2021
DOI: 10.6018/analesps.438431
|View full text |Cite
|
Sign up to set email alerts
|

The Gender Role Attitude Scale (GRAS) as an alternative for the crisis in measurement of attitudes towards gender roles in Latin America: A study in Chilean university students

Abstract: Hemos experimentado cambios socioculturales que han favorecido el desarrollo de actitudes de roles de género (GRA) más igualitarias. Sin embargo, actualmente la revolución en los roles de género está incompleta y la falta de equidad en las estructuras sociales limita las experiencias individuales en igualdad. Ante esta realidad, la comunidad científica exige un sistema modernizado para medir GRA. Presentamos adaptación, evidencia de validez factorial y convergente, precisión, efecto techo y piso, normas de int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…This scale (García-Cueto et al, 2015) showed evidence of validity in Chilean university students (Pérez et al, 2021). It evaluates stereotypical and transcendent attitudes towards gender roles through 17 items on a five-point Likert scale ranging from 1, ‘strongly disagree’, to 5, ‘strongly agree’.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This scale (García-Cueto et al, 2015) showed evidence of validity in Chilean university students (Pérez et al, 2021). It evaluates stereotypical and transcendent attitudes towards gender roles through 17 items on a five-point Likert scale ranging from 1, ‘strongly disagree’, to 5, ‘strongly agree’.…”
Section: Methodsmentioning
confidence: 99%
“…Esta escala (García-Cueto et al, 2015) mostró evidencias de validez en universitarios chilenos (Pérez et al, 2021). Evalúa actitudes estereotipadas y transcendentes hacia los roles de género mediante 17 ítems tipo Likert de cinco puntos desde 1, ‘muy en desacuerdo’, a 5, ‘muy de acuerdo’.…”
Section: Métodounclassified
“…As a measurement of attitudes to gender roles, we selected the Gender Role Attitudes Scale (GRAS; GarcíaCueto et al, 2015) because it is a recently developed instrument with evidence of reliability and validity for its use on Chilean university students ( Pérez et al, 2021 ), considering male and female gender roles in the family, social and occupational spheres. This makes the GRAS a good candidate to measure attitudes on the current Chilean sociocultural scene.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, although the phenomenon of the SDS may be present in both genders, a lower incidence among women could be expected because they are the ones who mainly suffer the negative side of this phenomenon. In addition, women accept to a lesser extent the social hierarchies that subordinate them ( Lee et al, 2011 ), while men show greater agreement with the traditional gender roles ( Pérez et al, 2021 ). The systematic review by Petersen and Hyde (2010) , and the review by Fugère et al (2008) , which included studies with samples from all the continents, support this premise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation